A morpholinium ionic liquid for cellulose dissolution. (5th October 2015) - Raut, Dilip G.; Sundman, Ola; Su, Weiqing; Virtanen, Pasi; Sugano, Yasuhito; Kordas, Krisztian; Mikkola, Jyri-Pekka
Highlights: Dissolution of cellulose in newly synthesized ionic liquids was studied. At 120 °C, [AMMorp][OAc] dissolve high amount (25–30 wt%) of cellulose with high DPn in 20 min. Importantly, 25 wt% cellulose with very high DPn (2082) could be dissolved. Structure and morphology of regenerated cellulose films were determined. Efficient recovery of [AMMorp][OAc] was demonstrated using water as an anti-solvent. Abstract: A series of substituted morpholinium ionic salts and allyl ammonium acetates were prepared. Amongst those, N -allyl- N -methylmorpholinium acetate ([AMMorp][OAc]) was found to dissolve cellulose readily without any pre-processing of native cellulose. At 120 °C, [AMMorp][OAc] could dissolve 30 wt%, 28 wt% and 25 wt% of cellulose with degree of polymerization (DP n ) – 789, 1644 and 2082 respectively, in 20 min. Importantly, SEC analysis indicated that no discernible changes occurred in terms of the degree of polymerization of the different celluloses after regeneration. Furthermore, when comparing the cellulose dissolution capability of these newly synthesized ionic liquids, it is evident that the combination of all three constituents – the morpholinium cation, the existence of an allyl group and choosing the acetate anion are essential for efficient cellulose dissolution. The structure and morphology of the regenerated cellulosic materials were characterized by SEM, XRD, TGA, CP/MAS 13 C NMR and FTIR, respectively.